Chemistry Learning Revolution: Problem Based Learning to Improve the Responsible Character Students in Atomic Structure Material - Haryanto Haryanto; Yusnidar Yusnidar; Harizon Harizon; Fuldiaratman Fuldiaratman; Elza Triani; Sri Wina Oktavia; Kowit Kittiwutthisakdi (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study aims to analyze the impact of the Problem-Based Learning (PBL) model on the development of students’ responsibility character in Chemistry education, with a specific focus on the challenging topic of atomic structure among 11th-grade high school students. Amid increasing concerns about character education in STEM subjects, this study seeks to fill the gap by exploring how active learning models influence affective outcomes alongside cognitive achievement. Methodology: A mixed-methods explanatory design was employed, incorporating a quasi-experimental approach with pretest-posttest control groups. Quantitative data were collected through self-assessment questionnaires, peer evaluations, and teacher observation sheets, while qualitative insights were gathered via semi-structured interviews and thematic analysis of student reflections. The triangulation of data sources provided a comprehensive view of how PBL implementation affects student responsibility. Main Findings: The findings revealed that students in the experimental group demonstrated significant improvements in their responsibility character compared to the control group. Higher posttest scores reflected positive behavioral changes in engagement, discipline, and task accountability during Chemistry learning activities. Qualitative data further supported that PBL encouraged students to take ownership of their learning process, collaborate effectively, and complete tasks with greater autonomy and diligence. Novelty/Originality of this Study: This research offers a novel perspective by applying PBL not only as a cognitive learning strategy but also as a tool for character development in complex Chemistry topics. It advances the understanding of integrative pedagogical models that simultaneously nurture academic proficiency and essential life skills, particularly responsibility, in secondary science education.